The Role of GP91phox-derived reactive oxygen species in the infection caused by Leishmania amazonensis: implications relative to the site of infection - Eric Henrique Roma de Lima (2013)
Leishmaniasis are a wide spectrum of diseases caused by parasites of the genus Leishmania. Because these are obligatory intracellular pathogens, infecting mainly macrophages and neutrophils, oxygen and nitrogen radicals production could be important factors in parasite killing. In the specific case of infection caused by Leishmania amazonensis, an important species causing cutaneous leishmaniasis in Brazil, there is no data in the literature demonstrating the effect of these radicals on the infection in vivo. Data from our group confirmed that nitric oxide has an important role in parasite killing in L. amazonensis infection, but superoxide and hydrogen peroxide do not appear to be associated with parasite killing in vivo. In this work, we showed that C57BL/6 mice deficient in the gp91phox subunit of NADPH-dependent oxidase of phagocytes (gp91phox-/-) infected subcutaneously with L. amazonensis develop larger lesions in the first weeks of infection and smaller lesions in the chronic phase of the disease when compared to wild type animals (WT). However, both WT and gp91phox-/- mice presented similar parasite loads. We detected higher levels of IL-17 in draining lymph nodes 8 weeks post infection (p.i.) and lower mRNA levels of IL-1 in the lesion site 12 and 16 weeks p.i. in gp91phox-/- mice. There are controversial data in the literature about the role of neutrophils in Leishmania infection, principally when different routes of inoculation are involved. Considering the relevance of these cells to ROS production and predicting important alterations of ROS effect when the inoculation route is changed, we compared the innate immune response generated on the most common used routes of parasite inoculation, the subcutaneous and the intradermal routes. However, we used the model of L. major infection, since this model is better established in the literature. Starting at 2h p.i., intradermal infection with L. major presented massive neutrophil recruitment and higher mRNA expression of CXCL-1 followed by intense recruitment of Ly6Chi inflammatory monocytes at 48h and 9 days p.i. compared to subcutaneous infection. This more intense inflammatory profile observed at the infected intradermal site also was accompanied by a more efficient parasite capture in this site. We observed a 10-fold increase in the number of infected cells at the times measured. In contrast, dendritic cells and macrophages represented the majority of infected cells in the subcutaneous site. Due this confirmed and important participation of neutrophils in the intradermal infection, we utilized this route of inoculation to determine the influence of ROS in our model of L. amazonensis infection. When infected intradermally, gp91phox-/- mice presented larger lesions starting at 4 weeks p.i. and a high degree of inflammation leading to a dense necrotic area and tissue loss without differences in parasite loads. Surprisingly, the levels of inflammatory cytokines did not change during the course of infection, but we did detect a large accumulation of neutrophils at the intradermal site. Increased neutrophil numbers in gp91phox-/- mice was associated with higher numbers and frequencies of necrotic neutrophils at 8 weeks p.i. and may be the major factor responsible for the inflammatory phenotype observed in these mice. These experiments suggest that oxygen radicals have an important role in L. amazonensis infection, controlling neutrophil flux to the lesion, impairing necrotic inflammatory death in these cells and consequently the inflammation of infected tissue. Moreover, the route of inoculation greatly influences the effect of reactive oxygen species (ROS) in L. amazonensis infection, since the major cells producing ROS, the neutrophils, play a prominent role only in intradermal infection. This is the first report to show the effect of ROS in Leishmania model closest to natural infection, indicating a more physiological way to study ROS in Leishmania infections.